Coding in the cot? Factors influencing 0–17s' experiences with technology and coding in the United Kingdom. (March 2022) - Gerson, Sarah A.; Morey, Richard D.; van Schaik, Johanna E.
Abstract: In the modern world, digital technology is all around us and our ability to engage with it efficiently and productively has implications for our success as individuals and as a society. The idea that children should hone their digital literacy skills through formal schooling has been recognized by educators and policy makers alike. Before children enter schooling, however, there are now an increasing number of ways for children to begin to learn about computers, robots, and coding. In this research, we present a survey of 729 UK parents (approximately 56% Welsh) of children between 0 and 17 years and asked them to report on whether they and their child had experience with different kinds of digital technology, with a particular emphasis on computer coding. We found that children are outpacing their parents in terms of coding experience before they even turn eight-years-old. Children are generally engaged with digital technology and coding earlier than their parents were as children (e.g., over 70% of two-year-olds use smart devices; nearly 40% of 7-year-olds have experience coding). Logistic regression analyses indicate that boys are significantly more likely to have experience coding than girls and children with parents who have experience coding are significantly more likely to have experience coding themselves. Parents who placed a relatively higher value on STEM education were also more likely to report that their children had experience coding. These findings align with literature on science capital suggesting that there are societal discrepancies in children's exposure to and experiences in STEM subjects. We also found that children with reported experience coding are also reported to show more interest in coding and robotics. This makes the fact that we find differences in exposure to coding prior to formal schooling even more problematic, as the discrepancies seen in early childhood may build up in later years in terms of motivation, engagement, and interest. Taken together, the current research shines light on the positive finding that young children are engaging with coding at early ages, but it also identifies potential problem areas regarding the breadth of exposure and experience. It highlights the need to ensure that the divide between those with and without science capital does not widen, allowing all children the freedom to obtain digital literacy that will help foster a more advanced future. Highlights: Modern children often gain their first experiences with computer coding prior to formal schooling. Experience coding (parent report) is higher for older (vs younger) children and for boys (vs girls). Experience coding (parent report) is higher for children whose parents have experience coding. Experience coding (parent report) is higher for children of parents who value STEM more.